PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI PENGUMPULAN DAN PENYAJIAN DATA KELAS V SEKOLAH DASAR MENGGUNAKAN MODEL PROJECT BASED LEARNING - Ridha Nabilah; R.Teti Rostikawati; Siti Nurjanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study was conducted with the aim of improving the learning outcomes of students of V-CSDN Bondongan class in the second semester (Genap) in Math subject of Data Collection and Presentation in the 2022/2023 lesson year. This type of research is class action research (PTK) using the Project Based Learning model as its main tool. The subjects of this study were 25 students of the V-CSDN Bondongan class. Male students numbered 12 people, female 13 people. Meanwhile, the object in this study is the improvement of the learning outcomes of V-C class students in Mathematics subjects of Data Collection and Preservation materials, after implementing the Project Based Learning model. This study was conducted in 2 cycles, each cycle having four stages; Planning, Implementation, Observation and Reflection. Researchers get data on research results through direct tests, observation of learning outcomes and observation of learning implementation. The data shows that the learning outcomes of students increased after the implementation of project-based learning models or Project Based Learning. It was proven strong with the achievement of students' learning outcomes in cycle I and cycle II that have improved. In Cycle I, the percentage of students' learning satisfaction was 44% and in Cycle II it was 84%. This indicates a 40% increase from cycle I to cycle II. This result also shows that the research on Bogor City Bondongan V-CSDN class was well achieved, namely the increase in students' learning outcomes in Mathematics subject of Data Collection and Preservation materials with Project Based Learning learning models.